Perbedaan Kemampuan Analisis Mahasiswa Antara Pembelajaran Berbantuan Schoology dan Edmodo Pada Mata Kuliah Fisika Biologi - Dewi Dewantara (IKIP Mataram, 2018)
One of the subjects in the physics education program is Biological Physics. The learning outcome of the course is able to analyze variously integrated and applied physics in understanding biology and be able to apply it. However, the duration of the lecture is not sufficient to train maximum analytical skills in each chapter and every meeting. Efforts to overcome this are by applying online classes to support face-to-face lectures in class with assistance from e-learning in the form of Schoology and Edmodo. The purpose of this study is to describe whether or not there are differences in analytical skills between students who carry out learning with the help of Schoology and with Edmodo's assistance. This type of research is quasi-experiment with Non-equivalent Group Posttest-Only Design methods. Samples were students of Physics Education, Lambung Mangkurat University who attended the Biology Physics course 2017/2018. Data was collected through posttest from classes that use Schoology and classes that use Edmodo, which consists of 4 questions to determine analytical skills with matching, specifying, analyzing error indicators, and generalizing indicators. Based on the results of the study, obtained sig (2-tailed) value of 1.66> 0.05. Therefore, the results of this study indicate that there is no difference in the ability of analysis between classes that carry out Schoology-assisted learning and Edmodo-assisted learning. Thus, both Schoology and Edmodo can be used as an aid in learning to train and improve students' analytical skills.